Improved photovoltage of printable perovskite solar cells via Nb5+ doped SnO2 compact layer. (13th January 2021) - Wang, Shiyu; Shen, Wenjian; Liu, Jiale; Ouyang, Tao; Wu, Yue; Li, Wenhui; Chen, Mingyue; Qi, Pengcheng; Lu, Yu; Tang, Yiwen
Abstract: The state-of-the-art perovskite solar cells (PSCs) with SnO2 electron transporting material (ETL) layer displays the probability of conquering the low electron mobility and serious leakage current loss of the TiO2 ETL layer in photoelectronic devices. The rapid development of SnO2 ETL layer has brought perovskite efficiencies >20%. However, high density of defect states and voltage loss of high temperature SnO2 are still latent impediment for the long-term stability and hysteresis effect of photovoltaics. Herein, Nb 5+ doped SnO2 with deeper energy level is utilized as a compact ETL for printable mesoscopic PSCs. It promotes carrier concentration increase caused by n-type doping, assists Fermi energy level and conduction band minimum to move the deeper energy level, and significantly reduces interface carrier recombination, thus increasing the photovoltage of the device. As a result, the use of Nb 5+ doped SnO2 brings high photovoltage of 0.92 V, which is 40 mV higher than that of 0.88 V for device based on SnO2 compact layer. The resulting PSCs displays outstanding efficiency of 13.53%, which contains an ∼10% improvements compared to those without Nb 5+ doping. Our study emphasizes the significance of element doping for compact layer and lays the groundwork for high efficiency PSCs.